Why didn’t anyone stop the bankers? Guðrún Johnsen: Down the Banking System: Lessons from Iceland - Conrad, Maximilian, 1975- (2014)
Bókadómur Despite the attention that the collapse of Iceland’s three major international banks Kaupthing, Glitnir and Íslandsbanki has attracted in the international mass media in the fall of 2008, most are still puzzled by the inability of key policy makers to avert the virtually complete collapse of the country’s financial system. How is it possible that three banks were allowed to grow so big that by the time they ultimately collapsed, they were indeed far “too big to fail”?